Rainfall infiltration: infinite slope model for landslides triggering by rainstorm - Agus Setyo Muntohar, Hung-Jiun Liao (Nat Hazards Springer, 2010)
Shallow slope failure due to heavy rainfall during rainstorm and typhoon is common in mountain areas. Among the models used for analyzing the slope stability, the rainwater infiltration model integrated with slope stability model can be an effective way to evaluate the stability of slopes during rainstorm. This paper will propose an integrated Green–Ampt infiltration model and infinite slope stability model for the analysis of shallow type slope failure. To verify the suitability of the proposed model, seven landslide cases occurred in Italy and Hong Kong are adopted in this paper. The results indicate that the proposed model can be used to distinguish failed and not-yet failed slopes. In addition, the proposed model can be used as the first approximation for estimating the occurrence time of a rainfall-induced shallow landslide and its depth of sliding.